Influence of tramadol on functional recovery of acute spinal cord injury in rats - CHAVES, Rosa Helena de Figueiredo (2019)
Purpose: To evaluate the influence tramadol on functional recovery of acute spinal cord injury in rats. Methods: Ten rats were divided into two groups (n = 5). All animals were submitted by a aminectomy and spinal cord injury at eighth thoracic vertebra. In control group, the rats didn’t receive any analgesic. In tramadol group, the rats received tramadol 4mg/Kg at 12/12h until 5 days by subcutaneous. Animals were following by fourteen days. Was evaluated the Basso, Beattie, Bresnahan scale (locomotor evaluation) and Rat Grimace Scale (pain evaluation) at four periods. Results: There no difference between the groups in locomotor evaluation in all periods evaluated (p>0.05) and in both groups there was a partial recover of function. The tramadol group show a lower pain levels at the first, third and seventh postoperatively days when comparing to the control group. Conclusion: The tramadol as an analgesic agent don’t influence on functional recovery of acute spinal cord injury in rats.